Health-Related Quality of Life Perception Among Older Persons with Non-Communicable Diseases in Primary Healthcare Facilities: A Qualitative Inquiry - Atim Fiona; Ndagire Regina; Chloe Nampima; Frank Kiyinji; Catherine Lwanira; Rose Clarke Nanyonga; Faustino Orach-Meza (International Journal of Global Health, 2024)
Background The understanding of older persons with non-communicable diseases (NCDs) regarding health well-being is paramount and can translate to increased self-efficiency, independence, and enhanced well-being. However, little is known about older persons' understanding of the concept of health-related quality of life (HRQoL) in Uganda. The study explored perceptions and unveiled understanding of older persons with NCDs on HRQoL in central Uganda. Methods This exploratory qualitative study design involved 23 participants recruited from selected Primary healthcare facilities in Central Uganda. Thematic analysis using an inductive approach generated themes that informed the study's qualitative findings. Results The study highlighted the physical domain as a key component of HRQoL, encompassing holistic well-being, lifestyle modification, and financial stability. To promote well-being and support a healthy aging journey, it is essential to adopt a person-centered approach that aligns with the perceptions of older adults on HRQoL.
Keywords: Health-Related Quality of Life